Smart capital in German start-ups: an empirical analysis - Dorothea Schäfer; Dirk Schilder (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
It is still an open question what kind of smart capital relational investors actually supply. We divide smart capital into several components and conduct a survey among 85 German suppliers of start-up finance. The results show that the degree of smartness is determined by the financial product used and also by the financiers institutional background, the duration of the investment and the stage of development of the firm being financed.
Keywords: G21; G24; D21; M13; O16; 330; Smart capital; start-up financing; venture capital; banks; Risikokapital; Private Equity; Unternehmensberatung; Unternehmensgründung; Deutschland